2017
DOI: 10.17140/hartoj-4-124
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of the Determinants of HIV Testing in Zimbabwe: Evidence from the Demographic and Health Surveys

Abstract: Introduction: Zimbabwe is still burdened with HIV epidemic and the government has an ambitious aim in the post-2015 era to end the AIDS epidemic by 2030. To achieve this, the government has set up the 90-90-90 strategic milestones to be achieved by 2020. It is a daunting task to increase HIV testing uptake from the current estimate of 56% to 90% to meet these targets. The current government's initiative requires an understanding of determinants of HIV testing. Objectives: The specific objectives of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
18
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 35 publications
9
18
2
Order By: Relevance
“…The magnitude from our study is greater than many findings from studies done in Burkina Faso, Ethiopia, Cambodia, and South Africa. 9,15,[20][21][22][23] But the current figure is less than the result drawn from the study done in Malawi. 10 Most of the studies reviewed clarified that the majority of the figures were less than those of the results obtained by the current study and this may have linkage with the duration when the studies were conducted, meaning that they were mostly done before the year of this study since in the most recent times the VCT for HIV uptake is expected to increase.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The magnitude from our study is greater than many findings from studies done in Burkina Faso, Ethiopia, Cambodia, and South Africa. 9,15,[20][21][22][23] But the current figure is less than the result drawn from the study done in Malawi. 10 Most of the studies reviewed clarified that the majority of the figures were less than those of the results obtained by the current study and this may have linkage with the duration when the studies were conducted, meaning that they were mostly done before the year of this study since in the most recent times the VCT for HIV uptake is expected to increase.…”
Section: Discussioncontrasting
confidence: 72%
“…Regarding wealth status, the odds of getting tested for HIV/AIDS for the rich males was 58.6% higher than for the poor. Different studies [14][15][16]20,28 also showed that rich people are more likely to accept HIV VCT as compared to the poor. This could be explained by different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…HIV VCT uptake among sexually active men in Ethiopia was estimated to be 45.69% (95% CI: [43.08%, 48.33%]). The magnitude of our study is greater than many ndings done in Burkina Faso, Ethiopia, Cambodia, and South Africa (9,15,(20)(21)(22)(23). But the current gure is less than the result drawn from the study done in Malawi (10).…”
Section: Discussioncontrasting
confidence: 74%
“…Regarding wealth status, the odds of getting tested for HIV/AIDS for the rich males were 58.6% higher than the poor. Different studies (14)(15)(16)20,28) also showed that rich people are more likely to accept HIV VCT as compared to poor people. This could be explained by different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Women's individual responses were nested in communities. Communities were represented by DHS primary sampling units of about 20–200 people because they are the most consistent measure of community between DHS data sets and have been used to represent community in a number of multilevel studies using DHS data .…”
Section: Methodsmentioning
confidence: 99%